Intracavitary electrocardiography for peripherally inserted central catheters tip location and nursing for a patient with persistent atrial fibrillation and acute left heart failure (1例持续性房颤伴急性左心衰患者腔内心电图定位下PICC置管的护理) - LIAO Lihong (廖丽红); SHI Lihua (施丽华) (中西医结合护理)
This paper summarized the experience of using intracavitary electrocardiography (ECG) for peripherally inserted central catheters (PICC) tip location and related nursing management for a patient with persistent atrial fibrillation and acute left heart failure. A multidisciplinary team was established to evaluate the feasibility and risk of PICC placement, and provide corresponding measures. In order to reduce the risk of catheter misplacement, the intracavitary ECG was used to guide the PICC tip location. The blunt dissection method was used for skin expansion to reduce the risk of puncture site bleeding after PICC catheter placement. Pressure dressing was carried out to prevent bleeding at local puncture area, and regular assessment was conducted to ensure effective use of PICC catheter. The catheter was successfully placed fir 162 d and no catheter-related complication was reported. (总结1例持续性房颤伴急性左心衰患者腔内心电图定位下经外周静脉置入中心静脉导管(PICC)的护理经验。护理重点: 术前多学科合作, 团队成员讨论PICC置管可行性, 评估置管风险, 提出应对措施; 术中使用超声联合腔内心电图定位技术实时监测导管尖端位置, 减少导管异位风险, 采用钝性分离方法代替传统扩皮刀扩皮以减少术后穿刺点出血; 术后通过局部加压包扎预防局部出血; 带管期间定期评估确保导管功能正常。导管成功留置162d, 无相关并发症发生, 完成治疗后拔除导管。)